Pengaruh Kualitas Pelayanan Dan Promosi Terhadap Kepuasan Pelanggang (Studi Pada Pembeli Di Toko Emas Sehati Dampit Kabupaten Malang) - Agung Sunanto; Abd Kodir Djaelani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstrack            This study aims to determine the effect of independent variables namely brand equity, attractiveness of advertising and word of mouth on the dependent variable, namely the purchasing decision at Matahari Departement Store Malang Town Square. The sample in this study was 95 consumers using purposive sampling method. The research instrument uses a questionnaire and is analyzed using multiple linear regression analysis.The result of this study indicate that brand equity variables, the attractiveness of advertising and word of mouth simultaneously and partially have an influence on purchasing decisions. This study contributes to the brand equity strategy, the attractiveness of advertising and effective word of mouth. Keywords : Brand Equity, The Attractiveness of Advertising, Word of Mouth, Purchasing Decision